Influence of rest intervals after assisted sprinting on bodyweight sprint times in female collegiate soccer players - Nealer, A. L.; Dunnick, D. D.; Malyszek, K. K.; Wong, M. A.; Costa, P. B.; Coburn, J. W.; Brown, L. E. (The Journal of Strength and Conditioning Research, 2017)
Speed is a crucial element an athlete must possess to be successful. In soccer, the ability to accelerate faster than your opponent can result in being first to reach a ball on a breakaway or stopping a counter attack. A unique way to train explosive movements is to evoke postactivation potentiation (PAP) in the working muscles. Traditionally, an overload stimulus with a long rest period is used, but a model using an overspeed stimulus with shorter rest periods is less understood. Therefore, the purpose of this study was to determine the acute effects of varied rest intervals after assisted sprinting on bodyweight sprint time. Twenty-four female soccer players were split into 2 groups: recreational (n:11; age:20 ± 1.67 year; ht:162.30 ± 4.35 cm; mass:61.02 ± 8.78 kg) and collegiate athletes (n:13; age:19.76 ± 0.83 year; ht:166.85 ± 5.98 cm; mass:61.23 ± 3.77 kg). All participants attended 5 separate sessions, performed a dynamic warm up, then executed one 20 m sprint (with 5 m splits) at 30% bodyweight assistance (BWA). They then rested for 30 seconds, 1, 2, or 4 minutes in random order, followed by one bodyweight sprint with no BWA. Baseline sprint times were measured without BWA on the initial session of testing. Results revealed no difference in sprint time for the full 20 m distance in either group. However, sprint time was significantly decreased for the 0-5 m split only for the athletes after 1 minute (1.15 ± 0.06 second) and 2 minute (1.16 ± 0.06 second) rest compared with baseline (1.21 ± 0.04 second). Therefore, trained athletes should rest 1 or 2 minutes after 30% BWA supramaximal sprinting for increased bodyweight sprint speed.